Technical Proposal signed between IICA and BECT: Project Title: IICA/BECT Future Farmers Project - IICA, Bridgetown (Barbados) (2021)
The Future Farmers Project was designed in collaboration with the Barbados Environmental Conservation Trust as an initiative for identifying and showcasing young local farmers involved in agribusiness, and to share best practices in agricultural innovation in the agrifood sector.